Perbandingan Efisiensi Waktu Pemrosesan Cuti Konvensional dan Digital Berbasis Web Terintegrasi Notifikasi Telegram - Nabil Abiyu Nawwar; Wakhid Kurniawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The administrative process of personnel leave applications in various higher education institutions is currently predominantly managed conventionally using physical forms. This manual approach frequently triggers various operational problems, such as processing time inefficiency, a high risk of misplaced documents, and approval delays caused by leaders not always being at the workplace. Although some institutions have transitioned to web-based digital leave systems, these systems are still considered ineffective because users are required to log in repeatedly just to check for status updates. Based on these conditions, a crucial research gap is identified. To date, no studies have focused on the addition of the Telegram Bot notification feature as a real-time solution while simultaneously conducting an empirical and quantitative comparison of processing time efficiency between manual governance and the digital system. To fill this gap, this study aims to design and develop a web-based leave application information system integrated with the Telegram Bot API and to measure the significance of its processing time efficiency. As a technological solution, this system utilizes the Webhook algorithm, which is capable of sending instant approval notifications directly to leaders' mobile devices. In its implementation, this study applies a quantitative experimental approach involving 30 testing scenario samples. The software's feasibility was first validated through the Black Box Testing method to ensure its functionalities operate correctly. Afterward, it was followed by comparative data analysis using the parametric statistical Paired Sample t-Test assisted by SPSS software. The test results show that all system modules have operated validly. Furthermore, quantitative measurement proves that the implementation of the system with Telegram notifications can drastically reduce the bureaucratic flow, lowering the average processing time from 370.33 minutes in the manual method to only 1.33 minutes. Statistical tests confirm that this efficiency difference is highly significant (Sig. 2-tailed = 0.000 < 0.05). The main contribution of this research is providing empirical evidence regarding operational time savings of more than 95%, as well as presenting a practical solution framework for institutions in adopting automation technology to achieve a modern, transparent, and responsive administrative governance.